The Effectiveness of Using YouTube as Learning Media in Teaching Greetings and Partings for 7th Grade Students of MTS Ma’arif Roudlotut Tholibin - Ummikultsum, Rosaaila; Suhono, Suhono; Pratiwi, Wiwied; Agustina Sari, Yeasy (Tapis: Jurnal Penelitian Ilmiah, 2024)
This study attempted to determine the teaching greetings and partings using YouTube as a media of learning at MTs Ma’arif Roudlotut Tholibin, the formulation of the problem in this proposal consists of a question about the use of YouTube as an effective learning media in teaching greetings and partings for 7th grade student of MTs Ma’arif Roudlotut Tholibin? The purpose of this research is to find out whether YouTube is effective as a learning media in teaching greetings and partings for 7th grade students of MTs Ma’arif Roudlotut Tholibin. This study uses the one-group pre-test post-test design method with pre-test and post-test. Data was collected using a test consisting of 15 multiple-choice questions and 5 essays. The population in this study were 7th grade students of MTs Ma’arif Roudlotut Tholibin in the 2022 academic year and researchers used purposive sampling taken from class VII, which consisted of 20 students as the research sample. Data were collected through tests. This study chose one class with the aim of the researcher wanting to provide opportunities for all students to better understand the greeting and partings material in class. The researcher wants to invite all students to take part in the greeting and parting material. The results of the study found that YouTube as an effective learning media was used in learning greetings and partings on the data that explained the post-test (7.6) was higher than the pretest (2.09). This shows the use of YouTube as an effective learning media in teaching greetings and partings for 7th grade students of MTs Ma’arif Roudlotut Tholibin.